Temperature drives elevational diversity patterns of different types of organisms in Qinghai-Tibetan Plateau wetlands - Bangjing Ding; Lian Feng; Sang Ba; Xiaoliang Jiang; Guihua Liu; Wenzhi Liu (iScience, 2023)
Summary: The spatial pattern and driving mechanism of biodiversity along elevational gradients are key topics in ecology. However, it is still unclear whether the multidimensional diversity of different types of organisms shows a similar response to elevation changes. Here, we measured the species and phylogenetic diversity of plants, bacteria, fungi, and microbial functional groups (nitrifiers, denitrifiers, methanogens, and methanotrophs) in 36 wetland sites on the Qinghai-Tibetan Plateau. The results showed that both species and phylogenetic diversity of plants, bacteria, and fungi exhibited a significant elevational gradient, in direct contrast to no significant diversity changes observed for denitrifiers, methanogens, and methanotrophs along the same altitude gradient. Our findings suggest that elevation and temperature were more likely to associate with the diversity of plants, bacteria, and fungi than the diversity of microbial functional groups, with important implications for assessing the effect of ongoing climate warming on biodiversity in Qinghai-Tibetan alpine wetlands.